A scoping review of smoking cessation pharmacogenetic studies to advance future research across racial, ethnic, and ancestral populations - Prom-Wormley, Elizabeth C.; Wells, Jonathan L.; Landes, Lori; Edmondson, Amy N.; Sankoh, Mariam; Jamieson, Brendan; Delk, Kayla J.; Surya, Sanya; Bhati, Shambhavi; Clifford, James (Frontiers in Genetics, 2023)
Smoking abstinence rates remain low despite the wide availability and accessibility of pharmacological smoking cessation treatments. In addition, the prevalence of cessation attempts and abstinence differs by race. Further, clinical treatment of nicotine dependence continues to be challenged by variability in effectiveness to promote abstinence, which may be due in part to current challenges in tailoring treatment to account for individual-level factors. There is support for customizing smoking cessation treatments for all smokers to increase abstinence rates. The contribution of genetic factors on smoking cessation have been consistently reported and the use of this knowledge holds promise. However, differences in allele frequencies of important genetic variants have been generally conducted in populations who often self-identify as White or who are determined to be of European ancestry. These results may not adequately capture variability across all smokers. This suggests that much of the current pharmacogenetic study results related to smoking cessation may not apply to all populations and clinical application of pharmacogenetic results may exacerbate health inequities by racial/ethnic groups. To date, pharmacogenetic research has rarely been evaluated from this perspective. This scoping review examines the extent to which racial/ethnic groups that experience disparities in smoking rates and smoking cessation are represented in the existing body of published pharmacogenetic studies of smoking cessation. We will summarize results by race/ethnicity or genetic ancestry across pharmacological treatments, and study designs. We will also explore opportunities and challenges in the real-world implementation of pharmacogenetics for smoking cessation, including practical barriers in utilization across diverse populations.